Pengaruh Capital Intensity, Leverage, dan Likuiditas dengan Profitabilitas Sebagai Variabel Moderasi Terhadap Agresivitas Pajak: Studi Empiris pada Perusahaan Sektor Industri Dasar dan Kimia yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Syahdilla Aulia Rahman; Cris Kuntadi; Rachmat Pramukty (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The purpose of this research is to analyze the effect of capital intensity, leverage, and liquidity on tax aggressiveness and the effect of profitability in moderating capital intensity, leverage, and liquidity on tax aggressiveness. This study uses a quantitative method, with data sources derived from the annual financial reports of companies listed on the Indonesia Stock Exchange from 2019 to 2023. This study examined 79 companies. In this study, the purposive sampling method was used to select samples; 36 company samples were selected over five years of observation, so that a total of 180 samples met the criteria. The results of the study indicate that capital intensity has a significant positive effect on tax aggressiveness, leverage has a significant positive effect on tax aggressiveness, and liquidity has a significant positive effect on tax aggressiveness. Profitability cannot moderate the effect of capital intensity and leverage on tax aggressiveness and profitability can moderate the effect of tax aggressiveness on liquidity.